PENGARUH DUE PROFESSIONAL CARE, PENGALAMAN DAN INDEPENDENSI TERHADAP KUALITAS AUDIT - Tiur Sitorus; Mira Pramudianti (Gapenas Publisher, 2022)
Public Accountansts in carrying out audits of financial statements gain the trust of clients and users of financial statements to prove the fairness of the financial statements presented. This study aims to examine the effect of due professional care, experience and independens on audit quality. The population in this study are auditors who work at KAP Surabaya. The number of KAP in Surabaya is 46 offices. The sample in this study were 60 auditors in 10 KAPs. Sampling using purposive samplinh method and analysis of research data using multiple linear regression analysis. Based on the results of the F test, it was found that the signifinance value of of the data was 0,000 so it can be concluded that due professional care, experience dan independence simulyaneously affect audit quality. Thus the first hypothesis can be supported. Meanwhile, in the –test, the signifinance value of the due professional care variable was 0,885>0,05 in the experience variable, the signifinance value was 0,410 > 0,05 and the independence variable had a signifinance value of 0,000< 0,05. So it can be concluded that the independence variable has an effect on audit quality, while the due professional care and experience variables have no effect on audit quality. Thus the fourth hypothesis is accepted and supported while the second and third hypotheses are not supported